Spatiotemporal evolution of multiple time scale precipitation in Yellow River Basin based on Köppen-Geiger Trend Indicator System - Hao Ke; Wenzhuo Wang; Zengchuan Dong; Xinhua Zhu; Zhuozheng Li; Chao Lü; Dawei Jin; Weilin Liu (Journal of Hydrology: Regional Studies)
Study region: The Yellow River Basin, situated in northern China. Study focus: Precipitation has shown significant variability over the past century, understanding its evolving trends helps addressing the impacts of climate change on local water resources. The Köppen-Geiger Trend Indicator System was proposed, which divides the study region into various climate zones and calculates indicators for quantifying precipitation trends. New hydrological insights for the region: Annual precipitation exhibits a significant decreasing trend in the Arid, steppe, cold (BSk) and Cold, dry winter, hot/warm summer (Dwa/Dwb) climate zones, while a significant increasing trend occurs in the Cold, dry winter, cold summer (Dwc) and Polar, tundra (ET) climate zones. Middle and lower reaches within the same climate zone exhibit differences in annual precipitation trends, highlighting the important impacts of geographical location. Monthly precipitation shows an increasing trend in winter (December–February) across most climate zones, indicating relatively stable changes in winter precipitation, while other seasons show changes between increasing and decreasing trends. Climate zones with decreasing annual precipitation also show greater variability in monthly precipitation, facing the dual challenges of decreasing water resources and extreme precipitation events.